Design of Image Processing System on Pressure Varied Using Interferometer Mach-Zehnder - Abdullah, Mujib; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2019)
Quantitative analysis and visualization of light becomes very important when we understand the nature of light, namely interference. This also applies to light-darkness conditions (such as the nature of light when an interference phenomenon occurs) and the application of light-propagating light (such as the wavelength traveled by light in the airspace or pressurized space). Because in the nature of light requires experimental observations and program algorithms that utilize the process of analyzing the nature of the light that occurs (interferometer). This study aims to design an image processing system design to obtain qualitative from the nature of light interference. Large quantitative interference ring measurement trials were carried out using the width measurement results on the observation board which varied at pressures of 0, -100, -200, -300, -400, and -500 which were given light sources from the red laser. From the measurement results obtained the difference between rings on the board in the form of area. The area can be compared manually to get the uncertainty of the sidewall fabrication that gives an error in the measurement.